Typologia konsumentów dóbr i usług kultury - Sobocińska, Magdalena (Typology of Consumers of Cultural Goods and Services, 2007)
The article presents the typology of consumers of culture goods and services. On the basis of primary data analysis it can be singled three types of culture consumers out. The first type of culture consumers treats the participation in culture as a form of individual development' and communications with creators, artists and other people. The second type of consumers is created by people for which participation in culture is the form of cultural education.The third type is built by consumers whose participation in culture is the form of relax.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (3); 2007; nr 1171, s. 56-64